Linker insertion-deletion mutagenesis of the v-src gene: isolation of host- and temperature-dependent mutants. - DeClue, J E (1989)
The host cell regulators and substrates of the Rous sarcoma virus transforming protein pp60v-src remain largely unknown. Viral mutants which induce a host-dependent phenotype may result from mutations which affect the interaction of pp60v-src with host cell components. To isolate such mutants and to examine the role of different regions of src in regulating pp60v-src function, we generated 46 linker insertion and 5 deletion mutations within src. The mutant src genes were expressed in chicken embryo fibroblasts and in rat-2 cells by using retrovirus expression vectors. Most linker insertions within the kinase domain (residues 260 to 512) inactivated kinase activity and transforming capacity, while most insertions in the N-terminal domain and at the extreme C terminus were tolerated. A number of mutations generated a host-dependent phenotype. Insertions after residues 225 and 227, within the N-terminal regulatory domain (SH2), produced a fusiform transformation in chicken embryo fibroblasts and abolished transformation in rat-2 cells; a similar phenotype also resulted from two deletions affecting SH2 (residues 149 to 174 and residues 77 to 225). Insertions immediately C terminal to Lys-295, which is involved in ATP binding, also produced a conditional phenotype. Insertions after residues 299 and 300 produced a temperature-sensitive phenotype, while insertions after residues 304 and 306 produced a host cell-dependent phenotype. An insertion which removed the major tyrosine autophosphorylation site (Tyr-416) greatly reduced transformation of rat-2 cells, a property not previously observed with other mutations at this site. We conclude that mutations at certain sites within src result in conditional phenotypes. These sites may represent regions important in interactions with host cell components.